Epifaunal Foraminifera in an Infaunal World: Insights Into the Influence of Heterogeneity on the Benthic Ecology of Oxygen-Poor, Deep-Sea Habitats - Venturelli, Ryan A.; Rathburn, Anthony E.; Burkett, Ashley M.; Ziebis, Wiebke (Frontiers in Marine Science, 2018)
A reduction in dissolved oxygen availability in marine habitats is among the predicted consequences of increasing global temperatures. An understanding of past oxygenation is critical for predictions of future changes in the extent and distribution of oxygen minimum zones (OMZs). Benthic foraminifera have been used to assess changes in paleo-oxygenation, and according to prevailing thought, oxygen-poor marine benthic habitats are dominated by sediment-dwelling infaunal foraminifera, while more oxygenated environments are populated with more epifaunal taxa. However, in this study we found elevated densities of epifaunal taxa in oxygen-poor habitats. A series of sixteen multicores were taken on depth transects (360-3000 m) across an OMZ in the Southern California Bight to investigate the ecology of living (rose Bengal stained) benthic foraminifera. Dissolved oxygen concentrations in bottom water at sampling sites varied from 21 mol/l to 162 mol/l. Sampling focused on bathymetric highs in an effort to collect seafloor surface materials with coarse sediments in areas not typically targeted for sampling. Mean grain size varied from about 131m (gravelly sand) to about 830μm (coarse sand with fine gravel). Vertical distribution patterns (0-2 cm) were consistent with those of conspecifics reported elsewhere, and reconfirm that Cibicidoides wuellerstorfi and Hanzawaia nipponica have a living preference at or near the sediment-water interface. As expected, assemblages were dominated by infaunal taxa, such as Uvigerina and Bolivina, traditionally associated with the supersaturated, unconsolidated mud, characteristic of OMZ habitats, suggesting that these taxa are not sensitive to substrate type. However, despite dysoxic conditions (21 mol/l to 28 mol/l ), epifaunal taxa comprised as much as 36 percent of the stained population at the five sites with the coarsest mean grain size, while other measured environmental parameters remained relatively constant. We suggest that these epifaunal taxa, including C. wuellerstorfi, prefer habitats with coarse grains that allow them to remain at or above the sediment-water interface. These results suggest that seafloor habitat heterogeneity contributes to the distribution of benthic foraminifera, including in low-oxygen environments. We submit that paleo-oxygenation methods that use epifaunal indicator taxa need to reconsider the dissolved oxygen requirements of epifaunal taxa.